Rosai Dorfman disease- A rare entity: Case report in North Indian male - Baruah, Ankur; Goyal, Parul; Ramesh, K. L. (Asian Journal of Medical Sciences, 2014)
Rosai Dorfman disease is a rare disease characterized by histiocytic proliferation of lymph node in young adults. We present here the case of a 67 years old Indian male presenting with lymphadenopathy and pyrexia of unknown origin for 16 months duration. Histopathological examination of lymph nodes revealed emperipolesis consistent with the diagnosis of Rosai Dorfman disease. The patient recovered with steroid treatment .Our case is one of the few cases of adult onset Rosai Dorfman Disease reported from India. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10288 Asian Journal of Medical Sciences Vol.6(3) 2015 87-90